Correlation between Tregs and ICOS-induced M2 macrophages polarization in colorectal cancer progression - Xu, Jiaxin; Gao, Yu; Ding, Yuting; Feng, Yunpeng; Chen, Jie; Zhang, Shenshen; Song, Xiaoyu; Qiao, Shifeng (Frontiers in Oncology, 2024)
Objective: To explore the mechanism by which Tregs promote the progression of colorectal cancer by inducing tumor-associated macrophages to polarize into M2 type via ICOS. Methods: Postoperative pathological tissues and clinical pathological data of 268 colorectal cancer patients who underwent initial surgery were collected. Immunohistochemistry (IHC) was used to detect the expression levels of ICOS, CD163 (a marker for M2 macrophages), and Foxp3 (a marker for Tregs) in cancerous, adjacent non-tumorous, and normal tissues. The relationship of ICOS, M2 macrophages, and Tregs in CRC with clinical pathological characteristics and pre-surgical tumor markers (such as CEA and CA199) was explored. Results: The expression levels of M2 macrophages and Tregs increased with tumor progression, while ICOS expression showed a decreasing trend. Compared to adjacent and normal tissues, the expression levels of ICOS, M2 macrophages, and Tregs were higher in CRC tissues. The expression levels of M2 macrophages and Tregs were significantly positively correlated with tumor markers, while ICOS expression was significantly